Detecting Partial Discharge in Cable Joints Based on Implanting Optical Fiber Using MZ–Sagnac Interferometry - Weikai Zhang; Yuxuan Song; Xiaowei Wu; Hong Liu; Haoyuan Tian; Zijie Tang; Shaopeng Xu; Weigen Chen (Sensors)
Detecting partial discharges in cable joints is critical for timely defect identification and reliable transmission system operation. To improve the long-term reliability and sensitivity of the sensing system, a novel method for cable joint monitoring based on implanting optical fibers within the joint structure is proposed. The electric field distribution of the optical fiber-implanted cable joint was simulated, followed by electrical performance tests, demonstrating that optical fiber implantation had a negligible effect on the electrical properties of the cable joint. A platform utilizing Mach–Zehnder–Sagnac (MZ–Sagnac) interferometry was developed to evaluate the frequency response of the implanted optical fiber sensor, with calibration performed on a non-standard curved surface. The results show that the average sensitivity of the sensor in the 10 kHz–80 kHz range is 71.6 dB, 2.0 dB higher than that of the piezoelectric transducer, with a maximum signal-to-noise ratio of 65.2 dB. To simulate common fault conditions in the actual operation of cable joints, four types of discharge defects were introduced. Partial discharge tests conducted on an optical fiber-implanted cable joint, supplemented by measurements using a partial discharge detector, demonstrate that the optical fiber sensors can detect a minimum discharge of 16.0 pC.